MODAL INTELEKTUAL, MANAJEMEN LABA, IMBAL HASIL SAHAM SAAT INI DAN MASA DATANG - Vicky Dwi Putra; Jaja Suteja; Erik Syawal Alghifari (JRAK, 2019)
Future stock returns are factors for investors to consider investing. This research aims to identify the influence of intellectual capital, earning management, and stock return toward future stock return in manufacturing companies of sub sectors food and beverages industry listed in Indonesia Stock Exchange period 2012 to 2017. This research used quantitative research methods with the sample as many as 7 companies. The sampling technique is used, as well as purposive sampling done based on certain criteria. The type of data used is secondary with analysis using panel data regression model with Eviews 10. The result shows that simultaneosly intellectual capital, earning management, and stock returns gave influence on future stock returns as much as 76.15%. Partially, intellectual capital had a positve but not significant, earning management had a negative and significant, stock returns had a positive and significant effects to future stock returns.